2002
DOI: 10.1159/000064319
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose 5-Fluorouracil / Folinic Acid in Combination with Three-Weekly Mitomycin C in the Treatment of Advanced Gastric Cancer. A Phase II Study

Abstract: Background: The 24-hour continuous infusion of 5-fluorouracil (5-FU) and folinic acid (FA) as part of several new multidrug chemotherapy regimens in advanced gastric cancer (AGC) has shown to be effective, with low toxicity. In a previous phase II study with 3-weekly bolus 5-FU, FA and mitomycin C (MMC) we found a low toxicity rate and response rates comparable to those of regimens such as ELF, FAM or FAMTX, and a promising median overall survival. In order to improve this MMC-dependent schedule we initiated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
29
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 25 publications
2
29
0
1
Order By: Relevance
“…This regimen may be considered for patients with colorectal cancer after pretreatment with 5-FU, irinotecan and oxaliplatin, but it is also likely to be a valuable, cost-saving and convenient treatment option even in earlier stages of colorectal cancer chemotherapy. Our results in gastric cancer patients, together with our earlier reported experience with infusional 5-FU/ mitomycin C combination therapy in this type of cancer (Hartmann et al, 2003;Hofheinz et al, 2002), suggest that the capecitabine/mitomycin C regimen could be considered as an alternative regimen for patients not suitable for cisplatin-based therapy.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…This regimen may be considered for patients with colorectal cancer after pretreatment with 5-FU, irinotecan and oxaliplatin, but it is also likely to be a valuable, cost-saving and convenient treatment option even in earlier stages of colorectal cancer chemotherapy. Our results in gastric cancer patients, together with our earlier reported experience with infusional 5-FU/ mitomycin C combination therapy in this type of cancer (Hartmann et al, 2003;Hofheinz et al, 2002), suggest that the capecitabine/mitomycin C regimen could be considered as an alternative regimen for patients not suitable for cisplatin-based therapy.…”
Section: Discussionsupporting
confidence: 57%
“…Hofheinz et al, 2004. Mitomycin (10 mg m À2 ) added every third week to weekly infusional high-dose 5-FU/FA yielded a response rate of 54%, and an overall survival of 10.2 months in patients with advanced gastric cancer (Hofheinz et al, 2002). In a randomised study comparing ECF (three-weekly epirubicin and cisplatin with protracted venous infusional (PVI) 5-FU 200 mg m À2 daily) to MCF (mitomycin 7 mg m À2 every 6 weeks and three-weekly cisplatin with PVI-5-FU 300 mg m À2 daily) in patients with advanced oesophagogastric cancer, both regimens resulted in equivalent response rates and survival (Ross et al, 2002), thus confirming the efficacy of combined infusional 5-FU and mitomycin C. In patients with either colorectal or pancreatic cancer, PVI-5-FU plus MMC resulted in a superior response rate (and an improved TTP in colorectal cancer) compared with PVI-5-FU alone (Ross et al, 1997.…”
mentioning
confidence: 99%
“…In gastric cancer, MMC (10 mg m À2 ) added every third week to weekly infusional 5-FU/FA yielded a response rate of 54%, and a median overall survival of 10.2 months (Hofheinz et al, 2002). Ross et al (2002) reported the results of a randomised study comparing ECF (3-weekly epirubicin and cisplatin in combination with protracted venous infusional (PVI) 5-FU 200 mg m À2 daily) to MCF (MMC 7 mg m À2 every 6 weeks and 3-weekly cisplatin with PVI-5-FU 300 mg m À2 daily).…”
Section: Discussionmentioning
confidence: 99%
“…The phase I study presented here was designed to evaluate the safety and tolerability of escalating doses of Caelyx in combination with weekly infusional 5-FU/ sodium FA and 4-weekly bolus MMC. 5-Fluorouracil and MMC were planned for use at 75% of the doses administered in our former studies (Hofheinz et al, 2002;Hartmann et al, 2003) and the Caelyx dose was escalated. Four-weekly Caelyx 20 mg m À2 can safely be combined with weekly infusional 5-FU/sodium FA and 4-weekly MMC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation